The qualitative characteristics of the waters of the Tigris and Diyala rivers in Baghdad (Journal of the College of Basic Education, 2022)
The study of the qualitative characteristics of surface water is one of the applied geographical studies that specialists in the field of water resources and spatial development attach great importance as it is one of the most common criteria in evaluating the quality of drinking water and the suitability of water for human and agricultural use and the health of ecosystems. The problem of water pollution in the city of Baghdad is not new, and this is due to the dumping of wastewater into rivers, especially in the Diyala River area, as the Tigris and Diyala rivers have been suffering from it for more than eighteen years, with an increase in the problem as a result of the increase in wastewater expenditures coming into the Diyala River, as well as the The lack of water supply for the two rivers from the upstream areas, and for the purpose of accurately defining the problem, four models were chosen on the Tigris River, which represent the first site at the city of Tarmiyah to represent the quality of the water coming from the Samarra Dam to the city of Baghdad ,And the second site is at the Tigris arm to represent the quality of water coming from Lake Tharthar to the city of Baghdad, the third site is at Al-Muthanna Bridge, and the fourth site is at Al-Shuhada Bridge. As for the Diyala River, two sites were chosen, the first near the April 9 pumping station, 10 km before the Al-Rustania station, and 23 kilometers from the mouth of the Diyala River in the Tigris River, for the purpose of representing the waters of the Diyala River before it was affected by the pollutants from the Al-Rustania station As for the second site, near the old Karguliya pumping station on the opposite side of the Al-Rustumiya station, and the site is 12 km from the mouth of the Diyala River in the Tigris River to know the impact of pollutants from the Al-Rustumiya station on the water quality of the Diyala River. Healthy in the untreated Rustamiya.